Is the impact of conventional risk factors the same in men and women? Plea for a more gender-specific approach. (1st July 2019) - Cifkova, Renata; Pitha, Jan; Krajcoviechova, Alena; Kralikova, Eva
Abstract: Cardiovascular disease (CVD) is the leading cause of death in women in developed countries. The traditional modifiable risk factors are able to explain the majority of CVD mortality. The aim of this review is to analyze gender-specific aspects of major conventional cardiovascular risk factors and to assess whether they have the same impact on CVD in women. Cigarette smoking remains the single largest preventable cause of cardiovascular morbidity and premature death worldwide. Women smoke less than men; however, smoking seems to be more harmful in women, particularly in oral contraceptive users. Obesity in the general population is more prevalent in women. Visceral adiposity is associated with insulin resistance and a higher risk of developing cardiovascular disease. Life expectancy in female diabetic patients is shorter than in men with diabetes; women with diabetes are also at higher risk of developing cardiovascular events. Changes of main lipid parameters in women are frequently associated with their hormonal status and/or hormonal treatment. Hypertension is highly prevalent in post-menopausal women and carries a higher risk of developing left ventricular hypertrophy, which, together with a greater increase in vascular and myocardial stiffness, results in a higher incidence of heart failure with preserved ejection fraction and a higher risk of developing stroke. The risk of abdominal aortic rupture is substantially higher in women. In conclusion, smoking, diabetes and hypertension seem to be more harmful in women. Therefore, the question is whether there should not be lower thresholds for initiating drug treatment in women with diabetes and hypertension. Highlights: There are gender differences in the prevalence and awareness of major risk factors. Smoking and diabetes seem to be more harmful in women. Subclinical organ damage in hypertension is more prevalent in women. Heart failure with preserved ejection fraction is more common in hypertensive women. Women are underrepresented in large clinical trials.